Предмет: Алгебра,
автор: mistermaks33333
Решите плз спасибки заране
Приложения:
Ответы
Автор ответа:
0
1) 5a - (3 + 5a^2) / (a + 1) = (5a^2 + 5a - 3 -5a^2) / (a +1) =
= (5a - 3) / (a +1)
2) (a^2 -b^2)/ b * b^2/ (ab + a^2) =
= (a - b)(a + b) *b / a (b + a) =(a - b)b / a
= (5a - 3) / (a +1)
2) (a^2 -b^2)/ b * b^2/ (ab + a^2) =
= (a - b)(a + b) *b / a (b + a) =(a - b)b / a
Автор ответа:
0
спасибочки
Похожие вопросы
Предмет: Математика,
автор: Аноним
Предмет: Қазақ тiлi,
автор: kirilldoob270679
Предмет: Математика,
автор: raimsikovfarhat
Предмет: Математика,
автор: ramil7704
Предмет: Обществознание,
автор: юляша312